Online Based Learning System (E-Learning) as Distance Learning Method Solutions: A Literature Review - Lestari Dwi; Salsabila S Kinasih; Hadi Supratikta (Journal of Investment Development, Economics and Accounting, 2024)
Purpose – This study aims to identify critical success factors influencing the effectiveness of e-learning systems in Indonesia. It examines the advantages of e-learning, such as flexibility and affordability, as well as challenges like the digital divide and varying digital skills. By reviewing literature from diverse sources, the research underscores e-learning's potential as a distance learning solution, emphasizing the need for educational institutions to address challenges to maximize its effectiveness in Indonesian educational settings.Methodology/approach This study employs a literature review method to identify critical success factors affecting the efficacy of e-learning systems in Indonesia. Data is gathered from scientific journals, books, and research reports to analyze the advantages (flexibility, affordability) and challenges (digital divide, varying digital skills) associated with e-learning.Findings The research results show that e-learning has several advantages as a distance learning solution, such as flexibility, accessibility, interactivity and affordability. However, e-learning also has several challenges, such as the digital divide, differences in digital skills, and learning motivation.Novelty/value This study contributes novel insights by specifically examining the factors influencing the effectiveness of e-learning systems within the Indonesian educational context. Unlike broader studies, it focuses on the unique challenges and opportunities present in Indonesia, including the impact of the digital divide, varying levels of digital skills among learners, and specific strategies for enhancing learner engagement and motivation. By conducting a comprehensive literature review drawing from scientific journals, books, and research reports, the study consolidates existing knowledge and identifies gaps that are crucial for informing policy and practice